Tinjauan Turidis Terhadap Pemulihan Nama Baik Bagi Terdakwa Yang Dinyatakan Bebas - Arjun Arjun; Juanrico Alfaromona Sumarezs Titahelu; Carolina Tuhumury (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Rehabilitation to restore the good name of a defendant who has been acquitted is a right that must be obtained by every defendant.Purposes of the Research: Based on the above background, the objectives to be achieved in this research are: 1. To examine and explain what are the legal reasons so that restoration of good name is possible in criminal cases. 2. To review and explain the implementation procedure in terms of obtaining the restoration of good name for a defendant. Methods of the Research: The research method used is a normative juridical research type. The problem approach used is the statutory approach and the conceptual approach. The sources of legal materials used are primary legal materials and secondary legal materials. The collection technique is through literature study and then analyzed through description using qualitative methods.Results of the Research: The results of the research and conclusions that the author can draw are showing how a defendant gets a recovery on his good name which has been regulated in Law No. 27 of 1983 concerning the implementation of the Criminal Procedure Code which contains procedures for rehabilitation so that a defendant can fulfill his rights in restoring his good name which has been further tarnished on charges that were not committed.